Tic Frequency Decreases during Short-term Psychosocial Stress – An Experimental Study on Children with Tic Disorders - Buse, Judith; Enghardt, Stephanie; Kirschbaum, Clemens; Ehrlich, Stefan; Roessner, Veit (Frontiers in Psychiatry, 2016)
It has been suggested that psychosocial stress influences situational fluctuations of tic frequency. However, evidence from experimental studies is lacking. The current study investigated the effects of the Trier Social Stress Test on tic frequency in 31 children and adolescents with tic disorders. A relaxation and a concentration situation served as control conditions. Patients were either asked to suppress their tics, or to “tic freely”. Physiological measures of stress were measured throughout the experiment. The Trier Social Stress Test elicited a clear stress response with elevated levels of saliva cortisol, increased heart rate, and a larger number of skin conductance responses. During relaxation and concentration the instruction to suppress tics reduced the number of tics, while during stress the number of tics was low, regardless of the given instruction. Our study suggests that stress might result in a situational decrease of tic frequency.